Effectiveness of Emotion Regulation Training Based on Grass Model on Reducing Rumination and Social Anxiety in Female Students with 60-Day Follow-up - Razagh Karami; Tayebeh Sharifi; Mohammad Nikkhah; Ahmad Ghazanfari (آموزش بهداشت و ارتقاء سلامت ایران, 2019)
Background and Objectives: Social anxiety and rumination are one of the most common emotional problems which affect the lives of different groups, especially young people. The aim of the present study is to examine the effect of emotion regulation training on reducing the rumination and social anxiety of second high school girl students in Shahrekord. Methods: The research method was quasi-experimental with pretest-posttest design. The statistical population of the study consisted of all second high school girl students in Shahrekord during the academic years of 2017-2018. 40 people participated in this study (20 participants in the experimental group and 20 participants in the control group), which were selected using a multi-stage cluster sampling method. The experimental group was under emotion regulation group training for eight 90-minute sessions. The data collection tools were Rumination Questionnaire and Social Anxiety Scale. Inferential statistics methods of repeated measures were used to analyze the data. Results: The results of data analysis indicated that emotion regulation training had a significant effect on reducing rumination (F=17/52, P<0/01) and social anxiety (F=20/16, P < 0.01). Findings also showed that the decrease in rumination (F=5/97, P<0/01) and social anxiety (F=14/57, P<0/01) in the follow up step was also maintained. Conclusion: According to the results of this study, emotional regulation in schools is very important and it is an important factor in decreasing the social rhythm and social anxiety of female students.